Application of Ortho-Bridge System after Femoral Bone Transport - Yang, Jinxing; Liu, Shuyu; Fu, Zicai; Xu, Qin; Xiong, Jianyi; Zhu, Weimin; Liu, Lijun (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2024)
The bone transport technique uses the principle of distraction-osteogenesis and fill bone defects with the aid of an external fixator. In order to evaluate the clinical effect of femoral internal fixation with Ortho-Bridge System after bone transport, 4 patients after femoral bone transport from October 2020 to October 2022 are studied in this paper. Among them, 3 patients ran refracture of femur after removal of the Limb reconstruction system, 1 patient just finish femoral bone transport and request internal fixation. The surgery results show that Ortho-Bridge System can be used in the situation that conventional Locking compression plate and intramedullary nail are not suitable due to anatomical variation after femoral bone transport. Key words: femoral fracture; Ortho-Bridge System; bone transport; postoperative complications of bone transport.
Keywords: Femur; fraktury femuru; Middle Aged; mužské pohlaví; Fracture Fixation, Internal; Adult; Postoperative Complications; externí fixátory; ženské pohlaví; Humans; External Fixators; vnitřní fixace fraktury; osteogeneze pomocí distrakčního aparátu; lidé středního věku; Osteogenesis, Distraction; Femoral Fractures; femur; dospělí; Female; pooperační komplikace; lidé; Male